Pengaruh Leverage, Free Cash Flow, dan Profitabilitas Terhadap Manajemen Laba Pada Sektor Consumer Cyclicals - Mohamad Zulman Hakim; Putri Okta Andani; Dewi Rachmania; Hamdani Hamdani; Mikrad Mikrad; Siti Chanifah (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2023)
Effect of Leverage, Free Cash Flow, and Profitability on Profit Management. Te purpose of this study was to empirically examine the Effect of Leverage, Free Cash Flow, and Profitability on Earning Management using the modified Jones Model. This research uses secondary data on consumer cyclicals companies that are listed on the IDX and generate profits in 2018-2021. The sampling technique used purposive sampling method and obtained as many as 28 companies with an observation period of 4 years. The dat analysis technique used is multiple linear regression analysis. The results of the analysis show that leverage has a positive effect on Earnings Management, but Free Cash Flow has a negative effect on earnings management and Profitability has a negative effect on earnings management.